KINSHIP OF WESTERN MUSIC BETWEEN DIFFERENT GENRES OF INDIAN MUSIC - Chauhan, Mukul; Srivastava, Kinshuk (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research paper shares the kinship between Indian music system and Western music system. Indian music has many different genres. Some famous genres are Ghazal, Bhajan, Thumri, Film music, Qawwali, Indian Pop and Folk music. All these genres are directly associated with western music system. Renowned Ghazal singer Jagjit Singh used to perform Ghazals with western instruments such as Guitar, Piano and Violin. The basic idea of presenting music to the audiences was never limited to Indian music. Western music system uses harmony to make music more exquisite. All the ghazals by Jagjit Singh are played with the arrangement of chords associated to the particular harmony needed for the Ghazal. Every piece of music that is composed has a particular chord combination attached to it to create a harmony. Therefore, Indian Ghazals composed in a Raga is also performed with a set of particular chords associated to it. Hence, we can say that western music system has a direct kinship with Indian music as it involves chords to create harmony.